2010
DOI: 10.1097/qad.0b013e328335cda3
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of symptomatic acute HIV infection in an outpatient ward in southern Mozambique: identification and follow-up

Abstract: Of patients reporting with fever, 3.3% were shown to be potentially due to AHI. High prevalence of AHI in southern African populations may warrant investigation of tools and target populations for AHI screening as a novel way to address HIV prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…HIV RNA was quantified by applying a multilevel pooling scheme of 10 samples/pool as described and validated in previous works. 19 A subgroup of HIV-negative time-matched controls was selected by computer randomization.…”
Section: Hiv Diagnosismentioning
confidence: 99%
“…HIV RNA was quantified by applying a multilevel pooling scheme of 10 samples/pool as described and validated in previous works. 19 A subgroup of HIV-negative time-matched controls was selected by computer randomization.…”
Section: Hiv Diagnosismentioning
confidence: 99%
“…Plasmodium falciparum-associated HIV-1 (Pf/HIV) infection has been described in many sub-Saharan Africa countries and data from these countries account for most of the available clinical data regarding this co-infection (Chalwe et al 2009, Davenport et al 2010, Kiyingi et al 2010, Mills et al 2010, Serna-Bolea et al 2010, Naniche et al 2011. A relevant issue in malaria-endemic regions is the identification of HIV/AIDS patients among suspected cases of acute malaria (Mills et al 2010, Serna-Bolea et al 2010. Furthermore, HIV-1 infection is a risk factor for receiving an incorrect diagnosis of malaria (Berg et al 2008).…”
mentioning
confidence: 99%
“…107(8): 985-992, December 2012 As leading causes of morbidity and mortality, malaria and human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) are two of the most important diseases in Africa (Idemyor et al 2007). Plasmodium falciparum-associated HIV-1 (Pf/HIV) infection has been described in many sub-Saharan Africa countries and data from these countries account for most of the available clinical data regarding this co-infection (Chalwe et al 2009, Davenport et al 2010, Kiyingi et al 2010, Mills et al 2010, Serna-Bolea et al 2010, Naniche et al 2011. A relevant issue in malaria-endemic regions is the identification of HIV/AIDS patients among suspected cases of acute malaria (Mills et al 2010, Serna-Bolea et al 2010.…”
mentioning
confidence: 99%
“…Previous studies have shown that rapid tests often fail to correctly identify weakly positive samples (19 ) such as those from recent HIV infections, which can constitute 0.3% to 3% of HIV-infected patients in high-risk populations with patients seeking care for bacterial sexually transmitted infections at sexually transmitted disease clinics and patients reporting fever in areas of high HIV prevalence (35,36 ). Furthermore, rapid tests operated in resource-limited settings have exhibited lower accuracy due in part to the difficulty in interpreting weak signals (18,19 ).…”
Section: Resultsmentioning
confidence: 99%